Slope Stability Analysis with Bore Piles for Landslide Prevention Using Plaxis LE 2D - Inabah, Redha Fatki; Sukamta, Sukamta (Diponegoro University, 2025)
The Rukoh Diversion Channel is an integral part of the Rukoh Dam, with the purpose of providing additional supply (supplement) to the Rukoh Dam reservoir of 15 m³/second. One of the components of the Rukoh Control Structure is a tunnel. The soil at the location of the Rukoh Diversion Channel tunnel consists of clay shale. Clay shale soil is a primary factor that causes landslides. Clay shale is a part of sedimentary rock, where this type of soil can undergo weathering in a short period when exposed to water, air, and sunlight. Several landslides have occurred at the inlet of the tunnel. Construction activities such as excavation and embankment can expose the soil, which may lead to a reduction in the shear angle of that soil. Landslide events at the inlet of the tunnel require management through soil reinforcement with bore piles using Plaxis LE 2D. This study aims to analyze the stability conditions of the slope in its existing state and with the reinforcement provided by bore piles. The factor of safety for the existing slope condition is 1.440, which is categorized as less than the required safety factor. The bore piles are planned to be 0.6 m wide and 8 m long. The bearing capacity analysis for the bore piles is 16147.21 kN, with the allowable lateral force provided by the bore piles using broms method being 54.348 kN. After the installation of the bore piles, the factor of safety for the slope is 1.868, which meets the minimum required threshold of 1.5.